شعرية الوصف وبناء الصراع في القصة الجزائرية قصة نوبة هستيرية لرحمة خطارنموذجا - خلود شاطي; ذياب فاطمة; خليفة دوش; فاطمة دحه (جامعة الوادي - University of Eloued, 2025)
الملخص: الوصف الشعري وبناء الصراع في القصة الجزائرية ، قصة هاما ختار الهزلية – كمثال – كنقطة انطلاق لبحثنا العلمي ومناقشة مشكلة كيفية ظهور الوصف الشعري وظهور الصراع في القصة، مع دراسة الجوانب الفكرية للرؤية السردية بدءًا بمقدمة، وهي هيكل البحث، يتضمن المخطط فصلين (نظري/عملي)، أما الفصل الأول، بعنوان ”المكونات السردية في القصة القصيرة الجزائرية“، فقد ناقشنا فيه قسمين وقسمنا البحث إلى عدة مواضيع_ القسم الأول بعنوان ”القصة القصيرة في السرد“، مع الأخذ في الاعتبار عناوينها الفرعية وعواملها وخصائصها الفنية، ثم مفهوم القصة القصيرة وأصلها وخصائصها والاتجاهات السائدة فيها، ثم ننتقل إلى جوهر الموضوع، وهو استعراض القصة القصيرة في الجزائر. _ أما الموضوع الثاني، فقد كان بعنوان ”دور المكون الوصفي في البنية السردية“، ومن خلاله ناقشنا، أولاً: مكونات البنية السردية في القصة، وثانياً: أهمية الوصف في القصة (تعريفه وأنواعه وخصائصه وتقنياته) - أما الفصل الثاني ، فكان بعنوان جماليات وصف الصراع في قصة الهستيريا ، وكان الأول بعنوان: خصائص وصف الصراع وظهوره في القصة ، تونشيني حول جوانب الوصف في الشخصيات والمكان (المكان، الفكر)، والوصف المختلط، وكذلك ظهور الصراع في أنواعه الخارجية والداخلية. عنوان القسم الثاني: الجوانب الفكرية واللغوية: في القصة ، من خلال ملاحظة المواقف ثم ربط العلاقة بين الشخصية والراوي ، ثم انتقلنا إلى الجوانب اللغوية والأسلوبية ، في محاولة لدراسة اللغة والأسلوب في القصة وأخيرًا ، تضمنت الخاتمة أهم نتائج البحث ؛ تلاها مباشرة مكتبة الباحث ، التي تضمنت معظم المراجع الواردة في البحث ، بالإضافة إلى فهرس الموضوعات ، وأخيرًا الملحق ، الذي تضمن القصة. Résumé de l'étude  Poetic des criptien and the constructien of confelict in the algerien stary ,the story ofhahma khattar’s hyslerical attach – as on example – wetooh it as a tepic far our scientific research and discussed the problem of haw, poetic des cription and the emergence of comflict appear in the story, while examining the intellectual aspects of the narratine vision Beginning witn an intre duction , which is the structure of the research, the plan includes two chapters (theoretical/ praetical), as fer the first chapter ,entitled , narratine components in the algerian shert slory, we dixussed two sections and diuided the researeh in toseueral topies_ the first section is entitled the hele of short storiesinnarratine , the taking inte account its subtitles, factors and chara cteristics of the ,art ,and then the concept, origin chara cteristies and trends of the shert story, then we get to the heart of the topic, which is an oueruien of the shert story in , ahgeria. _ Asfer the second topic ,it was entitled, the role of the descriptive component in narratine structure, and through it we dixeussed,ferst!; the components of narratine structure in the slory , and secand : the importance of des cription in the slory ( its definition , types , chara cteristics . tochnipues)- Asfar the secand chaptes ,entitled the aestheties of deseription of confliet in the story of hystions , the first entitled: characteristics of dexription of pxripation and the emergence of confilict in the stery, tonchiny on the aspects of descriptien in the characters and in the space ( spaace, tink ), blended descriptions , as wele as the emergence of confllict in bethe its external and internal types. The title of the secand section: the intellectnal and linguistic: aspects in the story , by okserving the situations and then linking the relationchip betweers the charcter and the narrater , then we moned to the linguistic and stylistic aspects , trying to study the language and style in the story Finally , a conclusion included the most important results of the research; followed immediately by the researcher’s library , which contaaned the most refernces inchded in the research , as wellas anindese of topics , and finally the appendix , which contained the slory...
دراسات أدبية
Keywords: شعرية الوصف،بناء الصراع ،القصة الجزائرية; Poetic description; conflict structure; Algerian story